Uranium - Past and Future Challenges : Proceedings of the 7th International Conference on Uranium Mining and Hydrogeology - Merkel, Broder J.; Arab, Alireza (Springer International Publishing : Imprint: Springer, 2015)
This book is the collection of papers from the latest International Uranium Mining and Hydrogeology Conference (UMH VII) held in September 2014, in Freiberg, Germany. It is divided to five sessions: Uranium Mining, Uranium and Phosphates, Clean-up technologies for water and soil. Uranium and daughter nuclides and basic research and modeling. Each session covers a wide range of related topic and provides readers with up to date research and solutions on those matters.